Strategi Dakwah Partisipatif sebagai Pendekatan Pengembangan Masyarakat Islam Berkelanjutan - Yeni Yasyah Sinaga (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
This research analyzes the implementation of participatory da'wah strategy in sustainable Islamic community development in Perawang, Riau. Using a qualitative descriptive method with a case study design, the research integrates Islamic theological values (syûrâ and ukhuwah) with the Participatory Rural Appraisal (PRA) method. The findings show that this approach deconstructs the dependency mentality of marginalized communities through four main stages: awareness-raising (infitah), organizing (tanzhim), concrete action (amaliyah), and participatory evaluation (istimariyah). This strategy successfully transforms the role of the congregation from passive objects of da'wah (mad'u) into subjects driving transformative change (da'i transformatif). Multidimensional impacts are evident in spiritual sustainability, economic empowerment (liberation from moneylenders through the mosque's baitul maal), and social cohesion as a cultural melting pot for the industrial community. Challenges such as initial cultural resistance and managerial limitations were addressed through exemplary da'wah and academic partnerships. The research formulates a Mosque Ecosystem-Based Transformative Participatory Da'wah Model that actualizes Maqashid asy-Syari'ah in a grounded manner for sustainable community self-reliance, demonstrating the effectiveness of participatory bottom-up approaches over top-down charitable models in empowering urban-industrial communities.